Analysis of the financial capability of the Bandung City Government West Java budget 2018 – 2021 - Gaus, Muh; Munandar, Agus (Gema Wiralodra, 2024)
This research was conducted to analyze the financial capability of the Bandung City government in West Java in 2018-2021. The approach used is financial ratio analysis which includes the ratio of independence, effectiveness, and efficiency. The data used is sourced from the Bandung City Government website from the Bandung City Budget realization report for the 2018-2021 period. The results of the analysis showed the value of independence ratio of 91.3%, effectiveness ratio of 88.4%, and efficiency ratio of 86.4%. The value of the independence ratio indicates the high financial ability of the government to finance its activities. A high effectiveness ratio indicates the country's high ability to generate revenue. High capability is indicated by a high-efficiency ratio in controlling the government budget. Overall, the results of the analysis show that the financial capability of the Bandung City government during the 2018-2021 period is in good condition. This is indicated by an independence ratio of 91.3%. The effectiveness ratio is 76%. The efficiency ratio is 86.4%. Therefore, the government needs to increase the efficiency ratio of 84.6%, this figure can still be increased so that its financial capabilities are more optimal in the future.